Protective antioxidant effects of grape seed extract in a cisplatin-induced hepatotoxicity model in rabbits - Kandemir, F. M.; Benzer, E.; Ozkaraca, M.; Ceribasi, S.; Yildirim, N. Cikcikoglu; Ozdemir, N. (Ecole Nationale Veterinaire Toulouse, 2012)
The present study was designed to investigate the protective effects of grape seed extract (GSE) on the liver oxidant / antioxidant status in cisplatin treated rabbits. For that, 18 male New Zealand rabbits were randomly allotted in 3 equal groups: in the control group, rabbits were injected with 0.9% saline whereas in the 2 other groups, they were intraperitoneally injected with cisplatin (5 mg/kg) (group CP) and in the 3rd group (group CP/GSE), they have also received GSE (250 mg/kg/day) by gavage for 6 days before and after cisplatin injection. The AST (aspartate aminotransferase), ALT (alanine aminotransferase), ALP (alkaline phosphatases) and GGT (gamma-glutamyl transferase) activities were determined in serum samples whereas the oxidant/antioxidant status (based on measurement of tissue MDA (malondialdehyde) and GSH content as well as glutathione peroxidase and catalase activities) and histopathological changes were explored in liver. In the cisplatin group, severe histopathological alterations, mainly mononuclear infiltrations, hepatocyte degeneration and necrosis, were associated to marked increases in serum activities of the liver enzymes and to tissue MDA accumulation coupled to reduction in antioxidant systems. In rat bits co-treated with GSE, liver injury was considerably attenuated, the antioxidant systems were quite preserved despite a weak and significant increase in MDA content compared to the healthy controls but serum enzyme activities were similar to the control values. These results evidence that oxidative stress is involved in cisplatin induced hepatotoxicity and that antioxidant compounds included in grape seed extract can strongly alleviate cisplatine-mediated liver injury in rabbits.
Keywords: Cisplatin; rabbit; hepatotoxicity; grape seed extract; oxidative stress; antioxidants